Tanggungjawab Perusahaan Angkutan Terhadap Kerugian yang Ditimbulkan Akibat Kelalaian Pengemudi Selama Kegiatan Penyelenggaraan Pengangkutan - I Wayan Werasmana Sancaya; I Made Aditya Mantara Putra (Kertha Wicaksana, 2021)
In fact, it can be observed that transport drivers often take actions due to deliberate action or negligence which result in losses to others, in this case either material or immaterial losses. This can be described as for example the actions of a driver who is driving his vehicle inappropriately in the sense that when carrying out his duties the driver is not fit, tired or under the influence of alcohol or illegal drugs which of course greatly affects his ability to drive a vehicle, resulting in accidents and cause harm to others. Based on this description, the researcher feels the need to examine the level and form of responsibility of goods transportation companies. This type of research used in this research is a type of empirical legal research. The result of the research is regarding the responsibility arrangement of the transportation company in the event of a loss caused by the driver during transportation activities at the Denpasar Cambodia Post Office and PT. Maharani Prema Sakti Denpasar refers to Law No. 22/2009 concerning Road Transportation Traffic, which is also stated in the work contract agreement between the transportation company and the driver. The form of company responsibility, namely the Denpasar Cambodia Post Office to the driver, the company before hiring the driver has included the driver with insurance. However, if the insurance costs are still insufficient to back up the financing of the driver who had the accident, the company will bear the shortage of costs. While the form of responsibility to the company PT. Maharani Prema Sakti Denpasar, which is responsible in accordance with the contents of the work contract agreement which states his responsibilities in a predetermined nominal.